The cost‐effectiveness of pharmacotherapy and lifestyle intervention in the treatment of obesity. (10th December 2019) - Lee, Minyi; Lauren, Brianna N.; Zhan, Tiannan; Choi, Jin; Klebanoff, Matthew; Abu Dayyeh, Barham; Taveras, Elsie M.; Corey, Kathleen; Kaplan, Lee; Hur, Chin
Summary: Background: The Food and Drug Administration has approved several pharmacotherapies for the treatment of obesity. This study assesses the cost‐effectiveness of six pharmacotherapies and lifestyle intervention for people with mild obesity (body mass indices [BMIs] 30 to 35). Methods: A microsimulation model was constructed to compare seven weight loss strategies plus no treatment: intensive lifestyle intervention, orlistat, phentermine, phentermine/topiramate, lorcaserin, liraglutide, and semaglutide. Weight loss, quality‐of‐life scores, and costs were estimated using clinical trials and other published literature. Endpoints included costs, quality‐adjusted life years (QALYs), and incremental cost‐effectiveness ratios (ICERs) with a willingness‐to‐pay (WTP) threshold of 100 000/QALY. Results were analysed at 1‐, 3‐, and 5‐year time horizons. Results: At each of the three follow‐up periods, phentermine was the cost‐effective strategy, with ICERs of 46 258/QALY, 20 157/QALY, and 17 880/QALY after 1, 3, and 5 years, respectively. Semaglutide was the most effective strategy in the 3‐ and 5‐year time horizons, with total QALYs of 2.224 and 3.711, respectively. However, the ICERs were prohibitively high at 1 437 340/QALY after 3 years and 576 931/QALY after 5 years. Deterministic and probabilistic sensitivity analyses indicated these results were robust. Conclusions: Phentermine is the cost‐effective pharmacologic weight‐loss strategy. Although semaglutide is the most effective, it is not cost‐effective because of its high price.